Características hidráulicas e energéticas de um pivô central - Barbosa, Brenon Diennevan Souza (2016)
The continuous monitoring of irrigation systems operational characteristics allows to the farmers to identify variations in the performance parameters of these systems and also orienting them to the necessity of replacement of worn components that could compromise the uniformity of water application and the energy efficiency of these systems. The aim of the study was to analyze, along a complete rotation of a 436.8 m long center pivot lateral line, the behavior the following characteristics: flow (Q), total dinamic head (HMT), active electric power (PEA), global efficiency (ƞg), specific consumption (CE), irrigation normalized specific consumption (CENI). The system was evaluated after six years of use, when the center pivot completed 8844 hours of operation on variable topography terrain, characterized by a vertical maximum downhill slope of 19.5m, a maximum uphill slope of 4.2m. Radial profiles of the spatial distribution of the pressure head along the lateral line were determined at 22 different angular positions assumed by the lateral line. At the lateral line position corresponding to the maximum uphill slope, the system water application uniformity (CUCH), as prescibed by the ABNT 14244 standard, was determined. The central pivot analyzed in this study operated with a mean flow rate of 231.95 m3 h-1, which represents a reduction of 4% in the design value. This reduction in flow rate may be associated with the increase on the observed head loss value along the main line (28m) which was much higher than the design value (13 m). This reduction in the system flow also caused a reduction in the observed PEA, the average observed value (98 kW) results in a 2.7% reduction in relation to the design value. Throughout the irrigated area, the observed pairs of HMT and Q values were always lower than catalog values. These factors also hampered the pressure head distribution along the lateral line: 9 profiles, out of 22 analyzed, presented values of minimum pressure head lower than the nominal value (7.02 m) of the pressure regulator valves. Despite the expected wear after 8444 hours of operation, the pumping unit global efficiency was satisfactory, reaching an average value of 72.46%, which represents a reduction of only 5% in relation to the design value. Despite the reduction in the pumping set global efficiency, the effect of the reduction of flow (Q) and total head (HMT) values was predominant in the determination of the mean EC value (0.424 kWh m-3), which was 1.8% below the design value. However, the observed mean CENI value (3.80 Whm-3m-1), which was 1.3% above the catalog value, reflected the fall in HMT, Q and global efficiency values. Even after 8844 h of operation, the system was able to present a CUCH value of 89.58%, which can be classified as a "good" uniformity of water application.